The Study on Students' Vocabulary Size - Yuliana T Wero; Karmila Machmud; Nurlaila Husain (Jambura Journal of English Teaching and Literature, 2021)
This study intends to know the vocabulary size of English Department Students in eight semesters. The population of this research is all students in English Department, specifically in eight semesters (class of 2013). This research used purposive sampling in taking the samples, and there are 21 students as the sample obtained from 122 students as the population. The method of this research is quantitative method. The instruments which the researcher used in collecting the data are fix test to measure how large students’ vocabulary size, that divided into two test; Receptive Vocabulary Size Test (RVST) and Productive Vocabulary Size Test (PVST). In analyzing the data, it is used numerical descriptive statistic to describe students’ vocabulary mastery first, and then calculate the vocabulary size. The result of this research shows that students’ receptive and productive vocabulary size were 3,110 words and 1,841 words respectively or in general around 4,905 words,with the receptive vocabulary knowledge was higher than productive vocabulary knowledge. However, it has shown a low result for the students who learned English for about eight semesters, it should be more than that.